Hubungan Hukum Internasional Sebagai Sumber Hukum Dalam Hukum Nasional - Feni Annisa; Aida Nur Fitriani; Mila Karmelia; Gema Refira Nugraha; Budi Ardianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
International agreements, which may include bilateral, regional or multilateral agreements, are recognized as laws that compel parties to comply (pacta sunt servanda). If an International Agreement has been ratified through a ratification process by a country, then the agreement has binding status and must be implemented by all parties and acts as a source of law in the decision-making process by law enforcement officials. In Indonesia, the same principle is applied to every International Agreement that Indonesia has participated in, whether it has gone through the ratification process or not, where the agreement has binding legal force for all parties involved.